SPK SAW PENENTUAN PAGELARAN TEATER TERBAIK - Dharyana Suryadijaya (Universitas Asahan, 2017)
Abstrack - The application of a Decision Support System (SPK) can help someone make accurate and well-targeted decisions. Many problems can be solved by using SPK, one of which is to analyze the determination of the best theater performances. The method that can be used for this Decision Support System is to use the Simple Additive Weighting (SAW) method. In determining the best theater performances in a performing arts festival, there are a lot of criteria that theater groups must have as a requirement to be the best theater group chosen by the jury. The jury has the criteria to determine who will be chosen to receive the award on the night of the best theater group awarding with the aim of getting quality quality artwork from a training process from the creators of art and the process of artistic creativity from a director. In this study, a case will be raised, namely finding the best alternative based on the criteria determined by the theater performance committee using the Simple Additive Weighting (SAW) method. The research was conducted by looking for the weight values for each attribute, then a ranking process was carried out that would determine the optimal alternative, namely the right theater group to get the best theater award from a theater of theater performances. Keywords - Simple Additive Weighting, Theater Festival, Decision Support System, Best Theater Show, Ranking.